Design of UWB microstrip patch antenna with variable band notched characteristic for WiMAX application - Mahfuz, M. M. Hasan; Soliman, Md Mohiuddin; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Sakib, Nazmus; Abdul Malek, Norun (IEEE, 2020)
Microstrip patch antenna (MPA) having Ultra-Wide Band characteristics is a worthy applicant in wireless communications. Mitigating EMI with the narrowband such as 5G lower band, Wi-MAX, WLAN, Satellite band lies in UWB region is a major research concern. This paper presents an UWB antenna containing variable band rejection for avoiding interference with Wi-MAX application. A simple rectangle patch antenna with defective ground structure is used to design UWB characteristics operating from 2.7 GHz – 13 GHz. Band rejections from 3.25 GHz to 3.8 GHz are obtained by utilizing semi-circular slot on radiating patch. Variable band rejection characteristic can be achieved in between 2.75 GHz – 4.4 GHz through altering the value of width of patch. The return loss and VSWR values over the band rejection frequency are close to 0 dB and greater than 2 respectively. In addition, the proposed UWB antenna obtained 85% radiation efficiency over the operating frequency, on the other hand, less than 53% radiation efficiency achieved over band rejection frequency. The proposed antenna is simple in design, compact in size, and efficient in radiation. Hence it is a good candidate on UWB antenna with band notch characteristic for Wi-MAX application.